2002
DOI: 10.1034/j.1398-9995.2002.057s71047.x
|View full text |Cite
|
Sign up to set email alerts
|

Olive allergen‐specific IgE responses in patients with Olea europaea pollinosis

Abstract: These results indicate that Ole e 1 and Ole e 2 are major allergens in patients with O. europaea pollinosis in our population. A combination of a few olive pollen allergens can substitute the crude extract for in vivo as well as in vitro diagnostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…4 of the 6 allergens analyzed are major allergens in this population (Ole e 1, 2, 7 and 10), and not in populations with a lower antigenic exposure. These results are in accordance with a different clinical phenotype as we previously described [8, 9]. These special characteristics together with our previous results [11,12,13] led us to analyze genetic polymorphisms related mainly to asthma and IgE regulation although the sample size was small.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…4 of the 6 allergens analyzed are major allergens in this population (Ole e 1, 2, 7 and 10), and not in populations with a lower antigenic exposure. These results are in accordance with a different clinical phenotype as we previously described [8, 9]. These special characteristics together with our previous results [11,12,13] led us to analyze genetic polymorphisms related mainly to asthma and IgE regulation although the sample size was small.…”
Section: Discussionsupporting
confidence: 71%
“…Among them, Ole e 1 is the most frequent sensitizing allergen [5, 6]. Besides Ole e 1, 9 additional allergens have also been isolated and purified from O. europaea pollen extract [7], some of which, e.g., Ole e 2 and Ole e 10, are major allergens in areas with high levels of pollen in the atmosphere [8, 9]. Furthermore, our previous studies have demonstrated a strong association between Ole e 10- and Ole e 2-specific sensitization and the bronchial asthma clinical phenotype as well as relevant associations among specific sensitizations and HLA class II antigens: Ole e 2 with DR7-DQ2, and Ole e 10 with DR2(15) antigens [9].…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, a population of 119 sera was assayed in ELISAs and prick tests, and prevalences of 31.9% and 37.8% were found, respectively. 35 In this context, Che a 3 is an atypical polcalcin because it showed reactivity to 46% of sera from individuals with chenopod allergy. The high prevalence of this panallergen in these patients might have a relationship with their characteristic polysensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the existence of seasonal rhinitis and/or bronchial asthma as well as a positive skin prick test to olive pollen allergen were the primary inclusion criteria for the study. The majority of olive allergic patients (ϳ90%) present associated taxonomically unrelated pollen allergies (31). However, inhibition assays of the IgE binding of olive-allergic sera to different pollen extracts suggest that O. europaea allergy should be a primary sensitization in those patients who are intensely exposed to its pollen (32).…”
Section: Discussionmentioning
confidence: 99%